RANCANG BANGUN APLIKASI GAME EDUKASI MENYUSUN HURUF (SCRAMBLE LETTER) BAHASA INGGRIS BERBASIS ANDROID UNTUK MENINGKATKAN KOSAKATA TINGKAT SD - Ahkam, Mizanul; Melisa, Anis; Kurniawati, Kurniawati; Umran, Munzir; Elfisa, Elfisa; Jakfar, Abu Bakar; Sara, Fahmi (Jurnal Teknik Informasi dan Komputer (Tekinkom), 2025)
The limited mastery of English vocabulary among elementary school students often becomes a barrier to their language learning progress, highlighting the need for engaging and interactive learning media. This study aims to develop an Android-based educational game application named Scramble Letter as an alternative tool to support vocabulary acquisition. The application was developed using Unity with an attractive interface and progressive gameplay consisting of Easy, Medium, and Hard levels. The research employed an experimental approach through observation, functional testing on various Android devices, and questionnaires administered to 21 elementary school students. The results revealed that over 90% of respondents agreed the application increased their learning motivation, enriched vocabulary, and improved spelling comprehension. In addition, functional testing demonstrated that the game operated stably without significant technical issues. These findings indicate that the Scramble Letter game is feasible and effective as a technology-based learning medium to enhance English vocabulary mastery among young learners.